KEHIDUPAN EKONOMI PETANI KELAPA (DESA SUNGAI PIYAI KECAMATAN KUALA INDRAGIRI KABUPATEN INDRAGIRI HILIR) - Hendry Revana; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Coconut is a fast growing crop in Indragiri Hilir Regency, especially in Sungai Piyai Village, where almost all of the people work as coconut farmers so that the economic growth of the community in Sungai Piyai Village depends on the ups and downs of coconut prices. Lat ely, the price of coconuts is known to be very alarming because the selling price is far from what farmers expect, given the high household needs and family education, currently the price of crested or peeled coconut ranges between IDR 700-1.200 , while copra coconut is around IDR 2.000-2.500 . So this causes the farmers to fret about their economic life. Based on these problems, through this research the writer aims to find out the actual condition of coconut farmers in Sungai Piyai Village, find out what are the obstacles faced by coconut farmers in Sungai Piyai Village, and find out how they face or overcome obstacles that occur. The research method used in this research is descriptive qualitative with the type of primary data that is data obtained directly based on interviews with research respondents and secondary data obtained through archives and documents at the research location. Data collection techniques through observation, in-depth interviews, and documentation. The number of informants in this study were 6 people. The results showed that farmers in Sungai Piyai Village relied heavily on the income of their coconut plantations or those they worked on because they were the only main and expected income. Constraints faced as a whole there are three factors including natural factors, pest factors and factors and price factors. To overcome this obstacle, farmers put siltation of joint ditches to prevent water from entering the plantation land, making trap equipment so that the land is not affected by pests, and saving household expenses so that the economic life of the community runs stable.Keywords: Economic Life, Farmers, Poverty